2017
DOI: 10.1007/s10897-017-0083-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Counselors’ Perception of the Effect on Practice of Laws Restricting Abortion

Abstract: In 2013, twenty-two states enacted seventy provisions restricting access to abortion. The legislation restricted access to abortions by instituting more regulations on providers and facilities, by prohibiting abortion prior to viability, by restricting funding available to patients and by requiring patients to wait a mandatory time period before having a procedure. Genetic counselors are trained to provide unbiased, comprehensive information in a non-directive style in order to allow patients to exercise their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
1
12
1
Order By: Relevance
“…Despite these statements from professional genetics organizations in support of access to abortion, there is little empirical evidence about how restrictive abortion laws impact prenatal genetic counselors and their patients who consider abortion. A small number of studies have been done on genetic counselors' knowledge of federal abortion laws (Graziani et al, 2018), attitudes toward abortion in general (Woltanski, Cragun, Myers, & Cragun, 2009), and their perceptions of the potential impact of proposed or newly implemented abortion laws (Cooney, Hercher, & Bajaj, 2017). A survey distributed in November of 2013 found that, in general, prenatal genetic counselors predicted that proposed or newly implemented abortion laws will increase stress for patients and providers (Cooney et al, 2017).…”
Section: The American College Of Obstetricians and Gynecologists (Acog)mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these statements from professional genetics organizations in support of access to abortion, there is little empirical evidence about how restrictive abortion laws impact prenatal genetic counselors and their patients who consider abortion. A small number of studies have been done on genetic counselors' knowledge of federal abortion laws (Graziani et al, 2018), attitudes toward abortion in general (Woltanski, Cragun, Myers, & Cragun, 2009), and their perceptions of the potential impact of proposed or newly implemented abortion laws (Cooney, Hercher, & Bajaj, 2017). A survey distributed in November of 2013 found that, in general, prenatal genetic counselors predicted that proposed or newly implemented abortion laws will increase stress for patients and providers (Cooney et al, 2017).…”
Section: The American College Of Obstetricians and Gynecologists (Acog)mentioning
confidence: 99%
“…A small number of studies have been done on genetic counselors' knowledge of federal abortion laws (Graziani et al, 2018), attitudes toward abortion in general (Woltanski, Cragun, Myers, & Cragun, 2009), and their perceptions of the potential impact of proposed or newly implemented abortion laws (Cooney, Hercher, & Bajaj, 2017). A survey distributed in November of 2013 found that, in general, prenatal genetic counselors predicted that proposed or newly implemented abortion laws will increase stress for patients and providers (Cooney et al, 2017). To our knowledge, limited research has focused on the perceived impact of current abortion restrictions on the practice of prenatal genetic counselors.…”
Section: The American College Of Obstetricians and Gynecologists (Acog)mentioning
confidence: 99%
“…This is consistent with previous research that studied the differences genetic counselors perceived in patient access to abortion after restrictive legislation was passed. Cooney et al, (2017) found that genetic counselors across all regions reported spending more time discussing new abortion legislation in counseling sessions, and some expressed that a decrease in access to abortion forces counselors to adapt a more directive style of counseling. In other words, genetic counselors reported that they felt the need to put more emphasis on their patients to decide quickly due to new legislation restricting access to abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few recent studies are available on how laws affect prenatal genetic counseling practice. A recent quantitative study by Cooney et al, (2017) surveyed genetic counselors to determine their perceptions of changes to their practice after the passage of restrictive abortion legislation. Cooney et al, (2017) sought to understand if genetic counselors in different regions of the United States noticed differences in their practice and their patients' ability to access abortion before and after certain types of abortion legislation were enacted in their state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation